TNF-α levels in hypertensive patients with type 2 diabetes mellitus with and without obesity - V.V. Zlatkina; T.M. Tikhonova; L.V. Bogun (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Patients with carbohydrate metabolism disorders and hypertension (HTN) are very often overweight and obese. Thus, the combination of HTN with obesity is extremely unfavorable, the frequency of which is constantly increasing. In turn, obesity, as an independent metabolic disease, is associated with hyperinsulinemia (HI) and insulin resistance (IR). The pathogenesis of IR in visceral obesity is heterogeneous and is due to the presence of genetic, gender, age, hormonal influences, and other factors. The development of inflammatory processes in obesity is accompanied by a parallel increase in the content of cytokines – mediators of inflammation, including tumor necrosis factor-alpha (TNF-α), which is associated with an increased risk of developing and progressing type 2 diabetes mellitus (DM), and a corresponding increase in the incidence of cardiovascular complications associated with this.